Pemanfaatan CaCO3 Terkalsinasi Dalam Pembuatan Biodiesel dari Minyak Biji Kapuk - Dwi Kartika; Inna Sofyana Ulyan Nisa; Dadan Hermawan (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Biodiesel production from kapok seed oil using calcined CaCO3 has been done. The objective of this study is to investigate the impact of varying concentrations of calcined CaCO3 catalysts on the biodiesel manufacturing process. The production of biodiesel involves two distinct processes, namely esterification and transesterification. The variation concentrations of the CaCO3 catalyst used in the experiment were 1%, 2%, 3%, 4%, and 5% (w/w). The results showed that the biodiesel nearly satisfied the ASTM D-1298 standard. The biodiesel generated using a CaCO3 catalyst with a concentration of 1% (w/w) and a contact period of 120 minutes exhibited the highest quality, with a biodiesel conversion rate of 41.57%.